2009
DOI: 10.1002/cne.22240
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral facial nerve axotomy in mice causes sprouting of motor axons into perineuronal central white matter: Time course and molecular characterization

Abstract: Generation of new axonal sprouts plays an important role in neural repair. In the current study, we examined the appearance, composition and effects of gene deletions on intrabrainstem sprouts following peripheral facial nerve axotomy. Axotomy was followed by the appearance of galanin+ and calcitonin gene-related peptide (CGRP)+ sprouts peaking at day 14, matching both large, neuropeptide+ subpopulations of axotomized facial motoneurons, but with CGRP+ sprouts considerably rarer. Strong immunoreactivity for ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“… 32 The galanin antibody was raised against the synthetic peptide, and staining is absent in the brains of galanin-knockout mice. 35 The nNOS antibody was raised against purified recombinant rat nNOS and labels a band of 155 kDa in Western blots of rat hypothalamus, while immunostaining is abolished by preabsorption with nNOS. 20 The parvalbumin antibody is directed against the mouse protein and recognises a band of 13 kDa on Western blots of mouse brain homogenates.…”
Section: Methodsmentioning
confidence: 99%
“… 32 The galanin antibody was raised against the synthetic peptide, and staining is absent in the brains of galanin-knockout mice. 35 The nNOS antibody was raised against purified recombinant rat nNOS and labels a band of 155 kDa in Western blots of rat hypothalamus, while immunostaining is abolished by preabsorption with nNOS. 20 The parvalbumin antibody is directed against the mouse protein and recognises a band of 13 kDa on Western blots of mouse brain homogenates.…”
Section: Methodsmentioning
confidence: 99%
“…We have reported that dorsal horn immunostaining with the galanin and NPY antibodies can be abolished by pretreatment with the corresponding peptides [51,59], and staining of neurons with the galanin antibody is absent from the brains of galanin knockout mice [34]. The nNOS antibody labels a band of 155 kDa in Western blot tests of rat hypothalamus, and staining is abolished by preincubation with nNOS [17].…”
Section: Methodsmentioning
confidence: 99%
“…The nNOS antibody labels a band of 155 kDa in Western blots of rat hypothalamus, and staining is abolished by pre-incubation with nNOS [ 49 ]. We have reported that dorsal horn immunostaining with the galanin and NPY antibodies can be abolished by pre-treatment with the corresponding peptides [ 50 , 51 ], and staining of neurons with the galanin antibody is absent from the brains of galanin knock-out mice [ 52 ]. The rabbit and goat parvalbumin antibodies were raised against mouse and rat parvalbumin, respectively, and recognise a protein band of the appropriate size on Western blots.…”
Section: Methodsmentioning
confidence: 99%